THE MOVEMENT FORM OF TRADITIONAL GAME (BUJA KADANDA) â€œDOU MBOJOâ€ RELATED TO PHYSICAL EDUCATION VALUES - Anwar, Anwar; Handayani, Oktia Woro Kasmini; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
This research aimed to describe and analyze the movement form of traditional game (buja kadanda) ?dou mbojo? related to physical education values. This research was a value relevance research with a qualitative research method and the approach model was phenomenology. The subject of this research was physical education and sports teacher, community leader and the cultural sector of Bima regency. Data collection techniques were observation, interview, documentation and triangulation. The result of this research were based on the findings and discussions of the movement form of traditional game (buja kadja) ?dou mbojo? related to physical education values. It was in accordance with the research problem which could be concluded that: the movement form occurred in traditional game buja kadanda was in line with the scope of physical education. The movement form was included  locomotor movements (such as walking / lampa, running / rai), nonlocomotor movements (such as jumping / nggoncu, spinning / wiri weki) and manipulative movements (such as hitting / maba, lambo, holding / parrying / taha). Furthermore, regarding to the physical education values were namely; cooperation, courage, obedience, respect, responsibility, fun, and excitement. The benefits of this research could be as a contribution to the science treasure in the socio-cultural field so that the community included children, teenagers and adults had knowledge about the physical education values and socio-culture in the traditional game (buja kadanda) ?dou mbojo? in Bima regency.